2020
DOI: 10.3389/fpsyt.2020.00506
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cultural Standards Promoted by the Mass Media as Predictors of Restrictive and Bulimic Behavior

Abstract: body image in this group. No sociocultural variables showed a direct impact on restrictive behavior among studied men. BMI had a positive and direct impact on individual body part satisfaction. These results may help improve prevention of eating disorders and dysfunctional eating behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 77 publications
2
28
0
4
Order By: Relevance
“…There were also no differences between Polish and Vietnamese women in terms of the intensification of restrictive behaviors and the pursuit of thinness. These results have been confirmed by other studies describing the importance of body dissatisfaction for the development of typical behaviors in eating disorders, such as in the Swedish studies by Forsén Mantilla and Birgegard [74], the Polish studies by Izydorczyk et al [32,75], and the Brazilian studies by de Carvalho, Alvarenga and Ferreira [49]. On the other hand, Rodgers and Melioli [51], in a review of 67 studies (emphasizing the important role of social media (i.e., the internet) and not taking into account psychological factors in these studies), indicated a significant relationship between the body image and behaviors related to the development of eating disorders in many countries in Europe, America, Australia, and Asia.…”
Section: The Characteristics Of Psychological Factors As Well As Restsupporting
confidence: 80%
“…There were also no differences between Polish and Vietnamese women in terms of the intensification of restrictive behaviors and the pursuit of thinness. These results have been confirmed by other studies describing the importance of body dissatisfaction for the development of typical behaviors in eating disorders, such as in the Swedish studies by Forsén Mantilla and Birgegard [74], the Polish studies by Izydorczyk et al [32,75], and the Brazilian studies by de Carvalho, Alvarenga and Ferreira [49]. On the other hand, Rodgers and Melioli [51], in a review of 67 studies (emphasizing the important role of social media (i.e., the internet) and not taking into account psychological factors in these studies), indicated a significant relationship between the body image and behaviors related to the development of eating disorders in many countries in Europe, America, Australia, and Asia.…”
Section: The Characteristics Of Psychological Factors As Well As Restsupporting
confidence: 80%
“…For example, Sanchez-Ruiz ( 39 ) studied the direct and indirect impact of sociocultural variables and mass media on the eating behavior of young adults (143 women and 101 men, aged 18–31 years), and the results confirmed that mass media pressure was an important predictor of this behavior. In another study ( 34 ), 514 Polish men and women were studied, and the results show that the pressure to conform to sociocultural body image and physical appearance standards had the most profound and direct influence on the development of restrictive eating behavior, appearing to negatively affect women's body image. Information searches on body image in mass media had the strongest and most direct impact on the development of bulimic eating behavior in/among women.…”
Section: Introductionmentioning
confidence: 99%
“…Após a aplicação de testes de atitudes alimentares (EAT-26) foram encontrados os seguintes resultados: desejo de corpo magro, menor nível de autoestima, maior número de contas em mídias sociais e maior importância dada às redes sociais. Esses resultados obtidos confirmam uma cobrança sobre as mulheres, sobretudo as mais jovens, que são ensinadas a manter um ideal de beleza muitas vezes inalcançável (Madureira, 2018) Segundo Izydorczyk et al (2020) a mídia influencia majoritariamente as mulheres mais jovens, sobretudo no final da adolescência. A variável mais significativa é a busca pela magreza em meninas com idade entre 12 e 15 anos e 21 e 29 anos seguida da insatisfação corporal que ocorre predominantemente entre os 12 a 15 anos.…”
Section: Discussionunclassified
“…Pela internet são escolhidos modelos e atitudes necessárias para se chegar ao sucesso e, ao mesmo tempo, quem não se identifica com esses modelos, automaticamente está fora do padrão estabelecido, logo, se tornando mais propenso a insatisfação corporal. A rejeição das singularidades causa um sofrimento psíquico e consequências extremas que podem refletir no comportamento alimentar (Izydorczyk, Sitnik-Warchulska, Lizińczyk, & Lipowska, 2020). Desta forma, o ato de comer deixa de ser influenciado apenas pelo âmbito social e ganha um novo integrante que é a normatização do belo propagado nas mídias (Vianna & Novaes, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation